Anaerobic digestion of the inedible oil biodiesel residues for value addition. (August 2017) - Khuntia, Himanshu Kumar; Chanakya, H.N.; Siddiqha, Asma; Thomas, Christine; Mukherjee, Niranjan; Janardhana, Naveen
Graphical abstract: Highlights: Biodiesel production form non-edible oil seeds generate a lot of residues. The residues all together hold more energy than biodiesel. Anaerobic digestion of these residues generates biogas that can be reused or traded. The residues contain compounds that inhibit the anaerobic digestion. The inhibition can be reduced by subjecting anaerobic digestion at lower S/I ratio. Abstract: Biodiesel from inedible oil seeds is a sought after renewable energy resource, however, per kg of biodiesel production from Pongamia pinnata ( PP ) and Jatropha curcas ( JC ) generates 7.88 and 5.83 kg residues, respectively in the form of pods, deoiled cakes (DC) and impure glycerol (IG). The pods and DC are lignocellulosic whereas IG contained 18–30% glycerol along with methanol, water, oil, soap, etc. The presence of inhibitory compounds in the residues such as lipids in DC; acid insoluble lignin in pods; methanol, lipids and soap in IG reduces the overall volume and rates of biogas production. The removal of methanol from IG enhanced the biogas volume by 10–20% and simultaneously reduced the lag phase by 50% at (S/I) ratio of 0.25. The co-digestion of IG with lignocellulosic residues at 1:1 ratio also increased the biogas yield and reduced the lag phase by over 50% without any need for supplementary nutrients. The total biogas yields from PP residues was 2–3 times higher than JC residues, offering relatively faster returns on investments. The biogas generation from the residues and its reuse as an energy source was estimated to reduce the biodiesel manufacturing costs by 40–80% and 19–40% in PP and JC, respectively.